An Analysis of Students' Interests and Biology Learning Outcomes in Offline Learning at SMA NEGERI 2 JEMBER - Oktafia, Riskana; Amartia, Chairiyah Yuli; Huda, Fahmi Nur Ahsan; Marhamah, Wasiatul (META: Journal of Science and Technological Education, 2022)
The goal of this research was to examine students' interests and learning results in a biology course at SMA Negeri 2 Jember using offline learning. This study is a qualitative descriptive study that employs a case study research technique. According to the findings of the questionnaire sent to students and instructors, 8 pupils and 2 teachers responded. The four markers of learning interest that are assessed are pleasure, interest, attention, and participation. The indicator of pleasure is a reasonably strong sign of learning interest since all students love engaging in biology lectures during offline learning because biology is relevant to daily life and can be done directly. The engagement indicator is the lowest of the indicators of student interest in learning because students in online learning lack the awareness to study independently at home because students spend a lot of time playing and do not study prior content that will be studied the following day.